Identification and Growth Characterization of a Novel Strain of Saccharomyces boulardii Isolated From Soya Paste - Hossain, Md Nur; Afrin, Sadia; Humayun, Sanjida; Ahmed, Monzur Morshed; Saha, Barun Kanti (Frontiers in Nutrition, 2020)
The nonpathogenic yeast Saccharomyces boulardii (Sb) has beneficial effects on the human intestine, thus applied as probiotics for the treatment of diarrhea and gastrointestinal diseases. This is the only commercialized yeast with the purpose of human medicine. Currently, little is known about their multiple mechanisms of actions. The S. boulardii yeast strain is isolated and identified by using the BIOLOGTM microarray identification system and morphologically. To understand the functional roles, the present study investigates the ability of this yeast to tolerate different concentrations of bile salt up to 2.5%, cell hydrophobicity, antioxidant, autoaggregation activity and simulated gastrointestinal digestion. The effect of different temperatures (up to 50ºC), pH (up to 8.0) and salinity (at best 7%) was also monitored on the growth and survival of the yeast cell. The physicochemical analyses revealed that S. boulardii could survive in stomach condition at pH 2.5, temperature 37ºC and 2% bile salt. Antibiotic susceptibility of S. boulardii was carried out using commercial antibiotic discs. The antimicrobial activity of the isolated S. boulardii against bacterial pathogens related to diarrhea diseases was in-vitro determined by the Well Diffusion method. The biosafety assay findings also claimed S. boulardii could be a potential probiotic. The experimental findings suggest that the isolated S. boulardii possesses excellent probiotic capacities as a biotherapeutic agent for antidiarrheal and gastrointestinal disorders.